2016
DOI: 10.1016/j.ijmecsci.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic modeling of structural components using embedded crystal plasticity constructive laws within finite elements

Abstract: a b s t r a c tPins are commonly used to join members of mechanical mechanisms. In order to maintain the integrity of the joint and prevent failure, there must be sufficient material of adequate strength around the pin hole to sustain the bearing and tear out loads from the pin connection. In this work, a multi-scale materials simulation model based on finite elements (FE) is developed for design and evaluation of materials for such applications. We specifically examine several constitutive models for simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Metals, such as Ta, Nb and ferritic steel, with a body‐centered cubic (BCC) crystal structure, have two or three families, making up 24 or 48 slip systems . Metals with hexagonal close packed (HCP) crystal structure like Mg, Zr, Be, or Ti metals as well as orthorhombic crystal structure like U, possess an even larger suite of slip families and systems . Moreover these low symmetry crystal structure metals deform by multiple variant of twins .…”
Section: Introductionmentioning
confidence: 99%
“…Metals, such as Ta, Nb and ferritic steel, with a body‐centered cubic (BCC) crystal structure, have two or three families, making up 24 or 48 slip systems . Metals with hexagonal close packed (HCP) crystal structure like Mg, Zr, Be, or Ti metals as well as orthorhombic crystal structure like U, possess an even larger suite of slip families and systems . Moreover these low symmetry crystal structure metals deform by multiple variant of twins .…”
Section: Introductionmentioning
confidence: 99%
“…Most pure metals with a face centered cubic crystal structure (e.g., Cu, Ni, Al) deform on one slip family 111 〈11 0〉, which contains twelve independently oriented slip systems [12][13][14].Metals, such as steel and most of refractory metals, with a body-centered cubic crystal structure, have two or three families, making up 24 or 48 slip systems [15][16][17][18][19]. Metals with a lower symmetry crystal structure, like hexagonal close packed Mg, Zr, Be, or Ti metals or orthorhombic U, possess an even larger suite of slip families and systems [20][21][22][23][24][25]. When plastically deformed, a crystal accommodates strain using a small subset of these systems.Which systems are activated, how many, and the distribution of shear among them are collectively referred to as slip activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally found that the multiple slip and twinning modes are active within individual crystals of a-U and such complex combinations are needed to explain its strong plastic anisotropy in macroscopic behavior [2,16,17]. Further, the slip modes differ in their sensitivity to temperature and strain rate leading to interesting and substantial changes in the constitutive response as temperature or strain rate changes [18].…”
Section: Introductionmentioning
confidence: 99%